エンガン カラ ドームフジ ヘ イタル ルート ゾイ ノ コウタク セツメン ノ ブンプ トクセイ - 古川, 晶雄; フルカワ, テルオ; 本山, 秀明; モトヤマ, ヒデアキ; 亀田, 貴雄; カメダ, タカオ; Furukawa, Teruo; Motoyama, Hideaki; Kameda, Takao (2008)
P(論文) 沿岸からドームふじ基地へ至るトラバースルート沿いにおいてサスツルギ,デューン,サーマルクラックといった雪面形態の出現頻度分布の観測を行った.光沢雪面について,1992年,1999年,2002年,2003年,2004年に行われたサーマルクラックの観察結果の比較を行い,サーマルクラックが数年にわたって観察される区間があることが明らかになった.これは光沢雪面が数年間にわたって存在する場合があることを示している. Frequencies of occurrence of snow surface features such as sastrugi, dunes and thermal cracks were observed along the traverse route from the coast to Dome Fuji Station. Comparison of data on thermal cracks in 1992, 1999, 2002, 2003 and 2004 indicates that glazed surface has existed over several years. departmental bulletin paper